Live stream marketing and consumers’ purchase intention: An IT affordance perspective using the S-O-R paradigm - Zhang, Lu; Chen, Min; Zamil, Ahmad M. A. (Frontiers in Psychology, 2023)
Recent years have seen a shift in the online retail industry toward a greater emphasis on live marketing. The growth of social media commerce on the internet demonstrates the popularity of Livestream shopping. Although there has been a rise in interest in studying live streaming, a comprehensive model describing why consumers are willing to consistently employ this novel sales format has yet to be developed. Hence, the present study develops a model to determine the factors influencing consumers' live-stream shopping intention by employing the affordance lens and S-O-R model. The online data was collected through the Wenjuanxing website from the users of live-streaming platforms such as Taobao.com, Mogujie.com, and JD.com. Results showed that (N=434): trust can be enhanced through visibility, metavoicing, trading affordance, guidance shopping and interactivity that consequently affects consumer purchase intention. In addition, this study highlights the theoretical and managerial implications for social commerce.